2011
DOI: 10.1016/j.beproc.2011.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Deciding when to “cash in” when outcomes are continuously improving: An escalating interest task

Abstract: A first-person shooter video game was adapted for the study of choice between smaller sooner and larger later outcomes. Participants chose when to fire a weapon that increased in damage potential over a 10 s interval, an escalating interest situation. Across two experiments, participants demonstrated sensitivity to the nature of the mathematical function that defined the relationship between waiting and damage potential. In Experiment 1, people tended to wait longer when doing so allowed them to eliminate targ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
73
1
2

Year Published

2013
2013
2016
2016

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 24 publications
(81 citation statements)
references
References 56 publications
5
73
1
2
Order By: Relevance
“…Future studies could focus on less verbal responses and interventions, by replacing the use of discrete rounds with verbal inputs (numbers from 1 to 9) through a free operant procedure, and the intervention messages by the differential reinforcement of some pattern of responses. Recent research has shown some progress with free operant data collection for social interaction tasks (Toledo et al, 2015), both for obtaining clearer learning curves and to avoid the instructional control and verbal mediation that arise from the experimental setting, which can overlap the effects of nonverbal contingencies on behavior (Young, Webb, & Jacobs, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Future studies could focus on less verbal responses and interventions, by replacing the use of discrete rounds with verbal inputs (numbers from 1 to 9) through a free operant procedure, and the intervention messages by the differential reinforcement of some pattern of responses. Recent research has shown some progress with free operant data collection for social interaction tasks (Toledo et al, 2015), both for obtaining clearer learning curves and to avoid the instructional control and verbal mediation that arise from the experimental setting, which can overlap the effects of nonverbal contingencies on behavior (Young, Webb, & Jacobs, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Another aspect to be considered in future studies is the type of reinforcers used in the experiment (points exchanged for money), which implies motivational issues that constrain the homogeneity between participants. It is possible that naturalistic conditions are more accurately simulated if the points obtained by participants entail more or less likelihood of success during the game than simply resulting in greater financial gain after participation (see Young, Webb, & Jacobs, 2011 for an example of a videogame-based task with does not imply financial gains).…”
Section: Discussionmentioning
confidence: 99%
“…
Abstract -Rhesus monkeys (Macaca mulatta) and capuchin monkeys (Cebus apella) performed a computerized inhibitory control task modeled after an "escalating interest task" from a recent human study (Young, Webb, & Jacobs, 2011). In the original study, which utilized a first-person shooter game, human participants learned to inhibit firing their simulated weapon long enough for the weapon"s damage potential to grow in effectiveness (up to 10 seconds in duration).
…”
mentioning
confidence: 99%
“…A recent study provided a novel approach to assessing human participants" capacity for inhibitory control in what was called a computerized "escalating interest task" (Young, Webb, & Jacobs, 2011). The task utilized a first-person shooter game in which the goal was to eliminate as many virtual enemies as possible using a simulated weapon.…”
mentioning
confidence: 99%
See 1 more Smart Citation